Sociological Survey on Humanised Communication Design of Public Hospital: A Case Study - Wang, Zhiyong; Yang, Liyao; Luo, Sirui (Scientific Research Publishing, 2016)
As humanised design served for the idea of “social responsibility”, this research takes a sociological survey on humanised design of in-patient departments of public hospital, as a case study, in order to present an example to value the significance of sociological survey upon reliable design. With well planned research target and communications, we take the survey methods as direct observation, questionnaire and group interview to obtain necessary information about needs of concerned people. Then, a series of design problems was found and the corresponding suggestions were made for improving solutions based upon comparative analysis. Finally, it reveals the strong relationship between social survey and improvement of humanised communication design with social responsibility.
Keywords: Sociological Survey; Humanised Communication Design; Public Hospital; Case Study